2010
DOI: 10.1186/1471-2474-11-210
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Dkk1 expression rescues dexamethasone-induced suppression of primary human osteoblast differentiation

Abstract: BackgroundThe Wnt/β-catenin pathway is a major signaling cascade in bone biology, playing a key role in bone development and remodeling. The objectives of this study were firstly, to determine the effects of dexamethasone exposure on Wnt/β-catenin signaling at an intracellular and transcriptional level, and secondly, to assess the phenotypic effects of silencing the Wnt antagonist, Dickkopf-1 (Dkk1) in the setting of dexamethasone exposure.MethodsPrimary human osteoblasts were exposed in vitro to 10-8 M dexame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 32 publications
3
47
0
Order By: Relevance
“…RANKL has been identified as a key regulator of the increased bone resorption; however, the specific regulators responsible for the decreased bone formation have not yet been identified. Several studies have demonstrated that glucocorticoids induce DKK1 expression in osteoblasts both in vitro (118) and in vivo (33), and that inhibition of DKK1 using small interfering RNA (siRNA) prevented the dexamethasone-induced suppression of primary human osteoblast differentiation (119). A significant induction of both DKK1 and sclerostin expression was observed in bones of mice treated with prednisolone for 56 d, which also resulted in significant negative effects on trabecular bone.…”
Section: Glucocorticoidsmentioning
confidence: 97%
“…RANKL has been identified as a key regulator of the increased bone resorption; however, the specific regulators responsible for the decreased bone formation have not yet been identified. Several studies have demonstrated that glucocorticoids induce DKK1 expression in osteoblasts both in vitro (118) and in vivo (33), and that inhibition of DKK1 using small interfering RNA (siRNA) prevented the dexamethasone-induced suppression of primary human osteoblast differentiation (119). A significant induction of both DKK1 and sclerostin expression was observed in bones of mice treated with prednisolone for 56 d, which also resulted in significant negative effects on trabecular bone.…”
Section: Glucocorticoidsmentioning
confidence: 97%
“…DKK1 also acts within the bone to specifically block Wnt/β-catenin signaling in osteoblasts, thereby inhibiting osteoblast development and activity [19]. DKK1 exerts this function by binding to either of the single-pass transmembrane receptor proteins Kremen 1 or Kremen 2 and also within the carboxyl-terminal propeller domains of either the LRP5 or LRP6 co-receptors [20].…”
Section: Introductionmentioning
confidence: 99%
“…HOBs were treated with 100ng/mL of HIV-1 gp120 (NIH AIDS Research and Reference Reagent Program) over a 48h time course. The HIV-1 gp120 used in this line of experiments was one of a number of agents being assessed simultaneously for osteogenic effects in HOBs and the same experimental controls were used for all agents analyzed 20 .…”
Section: Methodsmentioning
confidence: 99%
“…L-Wnt3a culture medium was supplemented with 400 µg/ml geneticin to maintain selective pressure. Conditioned medium from L-Wnt3a and control L-cells was collected according as per manufacturer’s protocols and as previously reported 20 . Cells were passaged 1:10 in 8 ml medium without geneticin and left to grow for 10 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation